Putting Derrida to Work: Review of Sarah Bezan and James Tink, eds., Seeing Animals after Derrida - Still, Judith (Humanimalia, 2020)
Sarah Bezan and James Tink, eds. Seeing Animals after Derrida. Lanham: Lexington Books, 2018. xxii + 250 pp. $105.00 (£70.00) (hc); $99.50 (£65.00) (e-book).